2008
DOI: 10.1529/biophysj.107.120626
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Diffusion Rate is Reduced in the Aortic Wall

Abstract: Endogenous nitric oxide (NO) plays important physiological roles in the body. As a small diatomic molecule, NO has been assumed to freely diffuse in tissues with a diffusion rate similar to that in water. However, this assumption has not been tested experimentally. In this study, a modified Clark-type NO electrode attached with a customized aorta holder was used to directly measure the flux of NO diffusion across the aortic wall at 37 degrees C. Experiments were carefully designed for accurate measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
0
29
0
2
Order By: Relevance
“…where c w is the concentration of NO in the arterial wall, D w the diffusivity of NO in the arterial wall (8.48 Â 10 210 m 2 s 21 ) and _ V w the reaction rate of NO [31]. The reaction rate is treated as a first-order rate expression, which is given by [32] …”
Section: Geometry Of the Modelmentioning
confidence: 99%
“…where c w is the concentration of NO in the arterial wall, D w the diffusivity of NO in the arterial wall (8.48 Â 10 210 m 2 s 21 ) and _ V w the reaction rate of NO [31]. The reaction rate is treated as a first-order rate expression, which is given by [32] …”
Section: Geometry Of the Modelmentioning
confidence: 99%
“…Factors that limit nitric oxide diffusion and therefore its half-life in biological systems include its interactions with soluble guanylyl cyclase and other proteins (e.g., hemoglobin), lipids and free radicals [1113]. When measured in isolated rat aorta, for example, its diffusion was shown to be four-fold smaller in an aortic wall than that in a homogeneous medium such as water [14]. It has also recently been reported that the cholesterol content in membranes decreases nitric oxide diffusion by 20 to 40% [12].…”
Section: Introductionmentioning
confidence: 99%
“…also demonstrated NOS activity in the larval midgut of L. pictus by NADPHdiaphorase staining. NO is also known to diffuse easily through membranes and into neighboring cells (Snyder 1992;Liu et al 2008), and to play other physiological roles in annelids besides regulating metamorphosis. Licata et al (2002) showed that NO regulates tissue homeostasis and salt-water balance in the epidermis of the earthworm Lumbricus terrestris, and endothelial NOS plays a role in repair of the nervous system in leeches (Shafer et al 1998) as well as in neurotransmission in the ventral nerve cord in the earthworm Eisenia fetida (Kitamura et al 2001).…”
mentioning
confidence: 99%